Chemical profiling of Trichocereus species from northern Argentina - Barbarich, María Florencia (2022)
The first nutritional profiling of all Trichocereus species of columnar cacti from northern Argentina is reported. Commonly called ‘cardones’ by locals, they are iconic elements of the flora and cultural heritage in the region. A general chemical characterization of the four species (T. atacamensis, T. terschekii, T. tarijensis and T.schikendatzii) was performed. Stem tissues for each species in terms of humidity, ash, protein content, carbohydrates, and reducing sugars, as well as phenols and anti-radical activity were profiled. The results constitute an advance in terms of general knowledge of these vulnerable and exploited Andean cacti and will contribute to ponder the most appropriate method of conservation and the possibility of bioprospecting and regulating its sustainable use.